Calming "Internet Arguments" with Design - Novin, Alamir (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2019)
"Internet arguments" are refer to users exchanging heated comments online. However, argumentation can also be beneficial for exchanging ideas on a topic with conflicting information. This is the situation with what Horst Rittel refers to as “wicked problem,” whereby solutions to problems are complex due to conflicting information. To assist discourse surrounding wicked problems, scholars created Computer Supported Argument Visualizations (CSAV). This exploratory pilot gathered user insight on when people prefer argumentation tools by asking participants to debate the complexities of Climate Change online. The results in this pilot study suggests that CSAVs for more formal argumentation might assist science journalism students with developing more informed opinions on the subject of Climate Change.